Negative Affect and HIV Risk in Alcohol and Other Drug (AOD) Abusing Adolescent Offenders - Lucenko, Barbara A. (2003)
Various depressive symptoms have been linked to elevated levels of HIV risk across diverse adult populations in multiple studies. However, this link has been examined in a much more limited manner among adolescents, despite an exceedingly heightened risk of both HIV and negative affect in this age group. To address the current lack of clinically pertinent knowledge in this area, we analyzed baseline data from 256 male and 107 female inner city, culturally diverse adolescent offenders. Relatively “high” and “low” negative affect subgroups were formed by conducting a median split on scores from the well-validated depressive affect scale of the Millon Adolescent Clinical Inventory (MACI). Compared to the low negative affect subgroup, the high negative affect participants reported significantly more sexual partners, unprotected sex, and increased susceptibility to HIV, as well as more marijuana, cocaine, and alcohol use (all p’s < .05). Although demonstrating better condom skills, negative affect participants reported less favorable attitudes towards using condoms, less knowledge about HIV transmission, and lower sexual self-efficacy than non-depressive participants. Symptoms of negative affect are therefore of particular concern for adolescents, who are at risk not only for generally acknowledged difficulties such as suicide, but also for multiple HIV risk factors. The theoretical and applied implications of these findings will be discussed.